Brain metastasis is predetermined in early stages of cutaneous melanoma by CD44v6 expression through epigenetic regulation of the spliceosome. (30th September 2014) - Marzese, Diego M.; Liu, Michelle; Huynh, Jamie L.; Hirose, Hajime; Donovan, Nicholas C.; Huynh, Kelly T.; Kiyohara, Eiji; Chong, Kelly; Cheng, David; Tanaka, Ryo; Wang, Jinhua; Morton, Donald L.; et al.
Summary Melanoma brain metastasis (MBM) is frequent and has a very poor prognosis with no current predictive factors or therapeutic molecular targets. Our study unravels the molecular alterations of cell‐surface glycoprotein CD44 variants during melanoma progression to MBM. High expression of CD44 splicing variant 6 (CD44v6) in primary melanoma (PRM) and regional lymph node metastases from AJCC Stage IIIC patients significantly predicts MBM development. The expression of CD44v6 also enhances the migration of MBM cells by hyaluronic acid and hepatocyte growth factor exposure. Additionally, CD44v6‐positive MBM migration is reduced by blocking with a CD44v6‐specific monoclonal antibody or knocking down CD44v6 by siRNA. ESRP1 and ESRP2 splicing factors correlate with CD44v6 expression in PRM, and ESRP1 knockdown significantly decreases CD44v6 expression. However, an epigenetic silencing of ESRP1 is observed in metastatic melanoma, specifically in MBM. In advanced melanomas, CD44v6 expression correlates with PTBP1 and U2AF2 splicing factors, and PTBP1 knockdown significantly decreases CD44v6 expression. Overall, these findings open a new avenue for understanding the high affinity of melanoma to progress to MBM, suggesting CD44v6 as a potential MBM‐specific factor with theranostic utility for stratifying patients.